(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to determine how the effect of intellectual capital on the profitability of banks listed on the Indonesia Stock Exchange (IDX). In this study, profitability is measured by return on assets and operating profit margin. The research sample used the financial statements of banking companies from 27 banks, for the 2017 and 2018 observation years. The company’s financial reports were obtained from the web. IDX. This study found that intellectual capital has a positive effect on company profitability, both in the form of return on assets and operating profit margin.